DOI: 10.11606/d.74.2011.tde-19092011-110737
|View full text |Cite
|
Sign up to set email alerts
|

Campo magnético pulsado na preservação de carne bovina moída

Abstract: This study aimed to evaluate the use of low intensity pulsed magnetic field (PMF) in the preservation of microbiological quality, color and oxidative stability of ground beef during aerobic refrigerated storage. Ground beef samples of chuck tender (Supraspinatus muscle) were exposed to PMF for 2 hours at frequencies of 1, 30 and 60 Hz or, in another step, they were exposed to a 1 Hz PMF for 2 hours or continuously for 12 days. Control samples were not exposed to PMF. Samples were stored at 4 o C for up to 12 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…They observed an improvement in electricity production with an increase in maximum tension by 20-27%, attributed to better bioelectrochemistry activity, possibly through the mechanism of oxidative stress. Lins [16] studied the use of a low-intensity magnetic field in the preservation of the microbiological quality, color, and oxidative stability of ground beef during aerobic refrigerated storage. The results of the study showed that a low intensity magnetic field has the potential to be used as an innovative technology, in combination with cooling, in the preservation of fresh meat.…”
Section: Introductionmentioning
confidence: 99%
“…They observed an improvement in electricity production with an increase in maximum tension by 20-27%, attributed to better bioelectrochemistry activity, possibly through the mechanism of oxidative stress. Lins [16] studied the use of a low-intensity magnetic field in the preservation of the microbiological quality, color, and oxidative stability of ground beef during aerobic refrigerated storage. The results of the study showed that a low intensity magnetic field has the potential to be used as an innovative technology, in combination with cooling, in the preservation of fresh meat.…”
Section: Introductionmentioning
confidence: 99%